2019
DOI: 10.1177/0272431619837376
|View full text |Cite
|
Sign up to set email alerts
|

Popularity Among Peer Role Models: A Moderator of Peer Victimization and Depressive Symptoms

Abstract: This short-term, longitudinal study examines evidence that the level of popularity among adolescents’ peer role models exacerbates the emotional impact of mistreatment by peers. We recruited 469 adolescents (255 boys, 214 girls; [Formula: see text] age = 12.7 years) from an ethnically diverse middle school and followed these youth for a 1-year period. We collected identical measurement batteries in two consecutive waves. Participants completed a self-report assessment of depressive symptoms, as well as a peer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…However, the prosocial effects of peer modelling on children may be weak or even non-existent because children aged 7–13 are less dependent on peers ( Lin, 2018 ). Nevertheless, we examined the possibility that behaviours modelled by peers also affect children, because studies have shown that children’s behaviours at this stage are influenced by peers to a certain extent ( Carr et al, 2016 ; van Hoorn et al, 2016 ; Lease et al, 2020 ; Luo et al, 2020 ; Chung et al, 2021 ; Nenniger and Müller, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the prosocial effects of peer modelling on children may be weak or even non-existent because children aged 7–13 are less dependent on peers ( Lin, 2018 ). Nevertheless, we examined the possibility that behaviours modelled by peers also affect children, because studies have shown that children’s behaviours at this stage are influenced by peers to a certain extent ( Carr et al, 2016 ; van Hoorn et al, 2016 ; Lease et al, 2020 ; Luo et al, 2020 ; Chung et al, 2021 ; Nenniger and Müller, 2021 ).…”
Section: Introductionmentioning
confidence: 99%